The Effect Of Earnings Per Share, Debt To Equity Ratio And Net Profit Margin On Stock Returns In Property And Real Estate Sector Companies Listed On The Indonesian Sharia Stock Index (Issi) For The 2018-2023 Period (International Journal of Scientific Research and Management (IJSRM), 2024)
The company’s financial performance is one of the factors that investors pay attention to in investing in the capital market. One of the investment instruments is stocks. The purpose of stock investment is to obtain a share retreat. This study aims to determine the effect of Earning Per Share, Debt to Equity Ratio and Net Profit Margin on stock returns in Properties and Real Estate sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2018 ̶ 2023 period. The analysis method used is the panel data regression method with the selected model being the Common Effect Model (CEM). The population in this study is all companies included in the Properties and Real Estate sector listed on the Indonesia Stock Exchange (IDX) for the 2018 ̶ 2023 period as many as 87 companies. The determination of the number of samples was carried out using the Purposive Sampling technique and determined as many as 16 samples of the Company. The results of the t test show that partially Earnings Per Share and Net Profit Margin have a significant effect on stock returns while the Debt to Equity Ratio does not have a significant effect on stock returns. The results of the F test show that simultaneously Earning Per Share, Debt to Equity Ratio and Net Profit Margin have a significant effect on stock returns in Properties and Real Estate sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2018 ̶ 2023 period.